2013
DOI: 10.1038/ncomms2348
|View full text |Cite
|
Sign up to set email alerts
|

The bipolar assembly domain of the mitotic motor kinesin-5

Abstract: An outstanding unresolved question is how does the mitotic spindle utilize microtubules and mitotic motors to coordinate accurate chromosome segregation during mitosis? This process depends upon the mitotic motor, kinesin-5, whose unique bipolar architecture, with pairs of motor domains lying at opposite ends of a central rod, allows it to crosslink microtubules within the mitotic spindle and to coordinate their relative sliding during spindle assembly, maintenance and elongation. The structural basis of kines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 49 publications
6
80
4
Order By: Relevance
“…1a) absolutely requires KIF11 52 , which is the only member of the kinesin-5 family in humans 53 . KIF11 is built from two homodimers arranged in an antiparallel manner so that identical pairs of heads project from each end of the tetramer, forming a microtubule cross-linker 52,54,55 . The C-terminal tip of the KIF11 tail also contributes to microtubule binding 56 .…”
Section: Centrosome Separationmentioning
confidence: 99%
“…1a) absolutely requires KIF11 52 , which is the only member of the kinesin-5 family in humans 53 . KIF11 is built from two homodimers arranged in an antiparallel manner so that identical pairs of heads project from each end of the tetramer, forming a microtubule cross-linker 52,54,55 . The C-terminal tip of the KIF11 tail also contributes to microtubule binding 56 .…”
Section: Centrosome Separationmentioning
confidence: 99%
“…In addition, it has been reported that the Xenopus laevis kinesin-5 Eg5 contains a non-motor MT binding site in its tail (24). Finally, it has been shown that the tail domains of the Drosophila melanogaster kinesin-5 Klp61F are located close enough to the motor domains to interact (25). A curious feature that was found for Klp61F is that the central BASS domain of the tetrameric stalk is constructed such that the two pairs of catalytic heads are rotated by 90°to each other (26).…”
mentioning
confidence: 99%
“…Like K1s, K5s have an N-terminal MD followed by a neck-linker (NL) that connects the MD to the rest of the motor. However, K1s are dimeric, whereas K5 tetramerization is mediated by the coiled-coil that follows the K5 NL and gives rise to a dumbbell-shaped molecule with pairs of MDs at either end (3,4). However, it is not simply the K5 tetrameric structure, with each MD pair taking ATPdriven steps toward the MT plus-ends (5), that is required for its mitotic functions: K5 MDs have specific mechanochemical properties that are matched to their spindle functions (6).…”
mentioning
confidence: 99%